OP0114 Inefficacy of Hydroxychoroquine in Primary Sjögren's Syndrome: Results at 12 Months of the Randomized Placebo-Controlled Trial of Plaquenil in Primary Sjögren's Syndrome. (23rd January 2014) - Gottenberg, J. E.; Ravaud, P.; Puechal, X.; Le Guern, V.; Sibilia, J.; Goeb, V.; Larroche, C.; Dubost, J. J.; Rist, S.; Saraux, A.; Devauchelle, V.; Morel, J.; et al.
Abstract : Background: Hydroxychloroquine (HQ, Plaquenil) is often prescribed in patients with primary Sjögren's syndrome (pSS). However, except a crossover trial, no controlled trial has ever evaluated HQ versus placebo. Objectives: Methods: 120 patients with pSS were randomly assigned to receive HQ (400 mg/j) or placebo for 24 weeks (controlled phase) and were all prescribed HQ between week 24 and week 48 (open extension). All patients fulfilled the AECG criteria. A favorable overall response (primary outcome criteria) was defined as the patient having >or= 30% improvement between weeks 0 and 24 in the values on 2 of the 3 patient's VAS evaluating dryness, pain and fatigue. Secondary end points were the evolution of the ESSDAI, the ESSPRI, Schirmer's test and unstimulated salivary flow, serum gammaglobulin levels, and of SF-36, HAD, PROFAD, and SSI. Serum interferon-regulated chemokines (CXCL10, CCL2 and CCL19) were assessed at baseline and W24 in the 45 patients with available serum. Results: Baseline characteristics of the 120 patients were as following: mean age 55.9 years, 91.7% of women, median disease duration: 5 years, anti-SSA positivity : 55.1%, patients with systemic involvement at enrollment: 30%. At 6 months, 19.2% of patients receiving placebo and 19.6% of patients treated with HQ had a favorable overall response (p = 0.9). At 12 months, 18.8% of patients treated for 6 months with placebo, then 6 months with HQ and 32.1% patients treated with 12 months with HQ were responders (p= 0.1). No significant difference was observed in any of the secondary outcome criteria. No significant difference was observed in patients with anti-SSA autoantibodies, high IgG levels, or systemic involvement. In patients treated with HQ, a trend towards a decrease of serum IgG was observed, as well as a significant decrease of IgM. In patients with HQ, a decrease in serum CXCL10 (from 50.5 to 35.8 pg/ml vs from 27.7 to 38.7 pg/ml under placebo, p=0.001) and CCL19 (from 241.6 to 160.9 pg/ml vs from 142.3 to 131.1 pg/ml, p=0.3), but not CCL2, was observed. In the HQ arm, all except 1 had detectable blood levels of HQ at 6 months. Baseline levels of HQ or of IFN-regulated chemokines were not associated with a favorable overall response. Tolerance of HQ was comparable to placebo. Conclusions: The results of this controlled trial did not show any evidence of short term efficacy of HQ in pSS. HQ induced a decrease in serum level of CXCL10 and CCL19, 2 IFN-induced chemokines but no association with response to HQ could be identified in any subgroup of patients. Disclosure of Interest: None Declared